2021
DOI: 10.3389/fphar.2021.735079
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin D Attenuates Pancreatic Injury Through Suppressing the Apoptosis of Acinar Cell via Modulation of the MAPK Signaling Pathway

Abstract: Chronic pancreatitis (CP) is a progressive fibro-inflammatory syndrome. The damage of acinar cells is the main cause of inflammation and the activation of pancreatic stellate cells (PSCs), which can thereby possibly further aggravate the apoptosis of more acinar cells. Saikosaponind (SSd), a major active ingredient derived from Chinese medicinal herb bupleurum falcatum, which exerted multiple pharmacological effects. However, it is not clear whether SSd protects pancreatic injury of CP via regulating the apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Previous evidence has illustrated that SSD attenuates renal cell apoptosis in septic mice 13 . SSD suppresses acinar cell apoptosis by inactivating MAPK signaling pathway, thereby ameliorating pancreatic injury 24 . These reports support our findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous evidence has illustrated that SSD attenuates renal cell apoptosis in septic mice 13 . SSD suppresses acinar cell apoptosis by inactivating MAPK signaling pathway, thereby ameliorating pancreatic injury 24 . These reports support our findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, recent studies showed that multiple miRs (miR-301, miR-200c, miR-149, miR-139, miR-34b) can affect the activity of PSCs during chronic pancreatitis, and modulation of their levels leads to PSCs apoptosis [ 70 , 71 , 72 , 73 , 74 ]. Moreover, studies demonstrated that targeting PSCs with antifibrotic or anti-inflammatory compounds in a form of siRNA or small molecules could prevent chronic pancreatitis progression [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. YAP1 has been shown to induce the activity of PSCs and stimulate pancreatic fibrosis during chronic pancreatitis [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, it was confirmed that the size of pancreas in CP patients decreased by nearly 20%, and in particular, the incidence of apoptosis in acinar cells increased by 10 times compared to that in the normal group ( Schrader et al, 2009 ). It has also been reported that the histological and inflammatory score of CP worsens as the expression of factors that cause apoptosis of acinar cells increases ( Singh et al, 2008 ; Li et al, 2021 ). Therefore, the inhibitory effect of glandular destruction is considered an important factor in improving CP.…”
Section: Discussionmentioning
confidence: 99%